Ablation of long-standing persistent atrial fibrillation - Mody, Behram P.; Raza, Anoshia; Jacobson, Jason; Iwai, Sei; Frenkel, Daniel; Rojas, Rhadames; Aronow, Wilbert S. (Annals of Translational Medicine, 2017)
Atrial fibrillation (AF) is the most commonly encountered arrhythmia in the clinical setting affecting nearly 6 million people in United States and the numbers are only expected to rise as the population continues to age. Broadly it is classified into paroxysmal, persistent and longstanding persistent AF. Electrical, structural and autonomic remodeling are some of the diverse pathophysiological mechanisms that contribute to the persistence of AF. Our review article emphasizes particularly on long standing persistent atrial fibrillation (LSPAF) aspect of the disease which poses a great challenge for electrophysiologists. While pulmonary vein isolation (PVI) has been established as a successful ablation strategy for paroxysmal AF, same cannot be said for LSPAF owing to its long duration, complexity of mechanisms, multiple triggers and substrate sites that are responsible for its perpetuation. The article explains different approaches currently being adopted to achieve freedom from atrial arrhythmias. These mainly include ablation techniques chiefly targeting complex fractionated atrial electrograms (CFAE), rotors, linear lesions, scars and even considering hybrid approaches in a few cases while exploring the role of delayed enhancement magnetic resonance imaging (deMRI) in the pre-procedural planning to improve the overall short and long term outcomes of catheter ablation.